A Snowball’s Chance… Methodological Considerations and Possibilities of Recruiting General Practitioners to Qualitative Research Through Large-Scale Group Chat Networks - Benjamin Saunders; Rosie Harrison; Carolyn A. Chew-Graham; Gwenllian Wynne-Jones (Qualitative Health Research, 2026)
In many qualitative studies, recruiting general practitioners (GPs), also known as family doctors or primary care physicians, has become increasingly challenging. This is due, in part, to the strain on GP capacity driven by greater service demand. In the United Kingdom, this demand coupled with increased general practice involvement in research has led to GPs experiencing research fatigue. This may be particularly apparent in qualitative studies, in which clinical impacts are often further upstream, and is yet more challenging if a research topic is seen as having lower clinical priority and/or is potentially controversial. In a recent qualitative study on work and health, we aimed to address this challenge through what we call large-scale professional/social network snowball sampling, using GP WhatsApp group chats. Using a GP gatekeeper to share study information in one of these groups, we could invite several hundred GPs. Following this, we asked GPs we interviewed to share study information in other group chats they were members of, allowing our snowball to grow increasingly large at a rapid pace. In this article, we reflect on this approach and argue that whilst this method can solve a practical recruitment problem, it also gives rise to numerous methodological considerations. This includes the credibility and trustworthiness of the research; the diversity of the sample recruited; consideration of saturation; and the increasingly problematic issue of ‘imposter participants’. We critically explore these issues and, through this, challenge the notion that snowballing sampling necessarily privileges the convenience of participant availability over sample depth and diversity.